Development of a Foundation Protocol for Feeding Complex Care Neonates and Enablers and Barriers to Its Implementation. Issue 3 (3rd July 2022) - Willson, Louise; Spence, Kaye
ABSTRACT: A continuing quality improvement project was undertaken as part of a twelve-month Clinical Neonatal Research Fellowship. The project was to develop a cue-based feeding protocol for cardiac surgical neonates with the aim of decreasing the time taken to establish full oral feeds. The aim was expanded to include all complex care infants in NICU as infants with other diagnoses may also benefit from consistency in feeding practices addressing suck feed and also nutrition goals. A review of the literature identified that feeding challenges are not always directly related to an infant's primary diagnosis. Feeding is not just an activity of daily living (oral milk feeding) but also a term used to describe a therapeutic intervention (enteral nutrition). There is potential mismatch between nutritional requirement, developmental readiness, and suck feed ability in all complex care infants. A six-stage flow diagram was developed that allows for multidisciplinary input. It is presented visually as "steps" increasing in height from left to right. Infant vital signs, hunger, and state cues inform decision-making around oral suck feeding. This includes the provision of "Feeding Associated Experiences." Individualized variations can be incorporated including existing feeding related protocols. The project demonstrated that it is possible to develop an inclusive, whole of admission feeding protocol that addresses oral suck feed and nutrition goals for complex care infants. Implementation strategies for the project were adapted from a comparable project. A theoretical domains framework was used to identify enablers and barriers to its implementation that will be addressed beyond the Fellowship term. Enablers were the developmental care workplace culture, the protocol's inclusiveness, a bed chart tool, and other visual references. Barriers to its success were the project unit's physical environment, the existing developmental care framework, and competing documentation. Adapting implementation strategies used in a similar setting is no guarantee of success. Identifying unique enablers and barriers to implementation will support modification to practice and ongoing change in units caring for complex care infants.